Mrg15 stimulates Ash1 H3K36 methyltransferase activity and facilitates Ash1 Trithorax group protein function in Drosophila - Huang, Chang (Nat Commun, 2017)
Ash1 is a Trithorax group protein that possesses H3K36-specific histone methyltransferase activity, which antagonizes Polycomb silencing. Here we report the identification of two Ash1 complex subunits, Mrg15 and Nurf55. In vitro, Mrg15 stimulates the enzymatic activity of Ash1. In vivo, Mrg15 is recruited by Ash1 to their common targets, and Mrg15 reinforces Ash1 chromatin association and facilitates the proper deposition of H3K36me2. To dissect the functional role of Mrg15 in the context of the Ash1 complex, we identify an Ash1 point mutation (Ash1-R1288A) that displays a greatly attenuated interaction with Mrg15. Knock-in flies bearing this mutation display multiple homeotic transformation phenotypes, and these phenotypes are partially rescued by overexpressing the Mrg15-Nurf55 fusion protein, which stabilizes the association of Mrg15 with Ash1. In summary, Mrg15 is a subunit of the Ash1 complex, a stimulator of Ash1 enzymatic activity and a critical regulator of the TrxG protein function of Ash1 in Drosophila.